Hubungan Social Support dan Vocational Skill dengan Career Adaptability di Era Revolusi Industri 4.0 Pada Siswa SMK Kompetensi Keahlian TITL Kota Malang - Dwi Mega Martasari; Setiadi Cahyono Putri; Yuni Rahmawati (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
The era of the industrial revolution 4.0 requires vocational students to adapt in a career (Career adaptability) (Y) because of the changing times, especially for the workforce. Therefore, vocational students as prospective workers must have vocational skills (X2) in soft skills and hard skills training. Besides sofftskill that is needed to increase the level of adaptation is social support (X1). This study aims to determine: (1) Description of X1, X2, Y, (2) Relationship of X1 to Y; 3) Relationship of X2 with Y, (4) Relationship of X1 and X2 with Y. The research method used is quantitative with research design descriptive correlational. The research sample of 95 students determined by referring to the saturation sampling technique. Variables X1, X2 and Y have the level of reliability in sequence are 0.761, 0.766. and 0764. Sequentially the Effective Contribution Value at X1 and X2 is 6.4% and 13.8%. Consequently the Relative Contribution Value at X1 and X2 was 31.68% and 68.32%. The conclusions of the results obtained from this study are (1) X1, X2, and Y in the medium category; (2) there is a positive and significant relationship between X1 and Y, X2 and Y, and X1 and X2 simultaneously with Y.